PENERAPAN GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN - Bella Syafrina Qolbiatin Faizah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2020)
The industrial revolution era resulted several of companies trying to produce products for human needs. These products produce waste where the waste can be one of the problems that occurs when the management building is damaged. This research aims to examine the effect of applying green accounting to financial performance. Green accounting focuses on environmental activities, green prooduct, and environmental performance using PROPER, while financial performance uses net profit margin. The sample selection using a purposive sampling technique that uses certain criteria about 24 companies in four periods. Data analysis techniques used multiple linear regression analysis. The results of this study indicate that green accounting has no effect on financial performance which is measured using a net profit margin.